Experimental aluminium encephalopathy: quantitative EEG analysis of aluminium bioavailability. - Cutrufo, C (1984)
Single oral doses of aluminium hydroxide (50 to 200 mg/kg) were found to induce in mice a dose-dependent diminution of the power of the 7.5 to 12 Hz frequency band, with a parallel dose-dependent increase of aluminium content in the brain, as early as 45 min after administration, and indicated that aluminium hydroxide is readily absorbed through an empty stomach or duodenum and is able to induce alterations of background EEG rhythms at doses equivalent to the ones used in human therapy. These data suggest that the EEG disturbances of the background type, (which are observed during the early stage of dialysis encephalopathy in man), may be partly due to a pharmacological and therefore reversible effect induced by an increase in aluminium level in the brain.